MENGUATNYA AUTOCRATIC LEGALISM: MELEMAHNYA KONSOLIDASI MASYARAKAT SIPIL UNTUK PELEMBAGAAN DEMOKRASI - Ramadhanil, Fadli; Kurnia Ilahi, Beni (UNIB Press, 2025)
Levitsky and Ziblatt emphasize that threats to democracy often occur gradually through mechanisms that are legal but fundamentally weaken the system. This phenomenon is called autocratic legalism: the use of law to legitimize undemocratic actions. This phenomenon highlights how policies that appear legitimate can be abused to perpetuate power or reduce public participation space. Once all constitutional constraints have been loosened, those in power can easily use legal instruments so that their actions appear legal. In reality, this phenomenon—mutatis mutandis—weakens the consolidation of civil society in the institutionalization of democracy and even pushes it toward authoritarianism. This is exactly the condition currently occurring in legislative practice in Indonesia. Laws are made solely to fulfill the needs and desires of a small group of political elites. Examples include revisions to the KPK Law (Anti-Corruption Commission) and the State-Owned Enterprises (BUMN) Law, and the enactment of the new Capital City (IKN) Law—all of which demonstrate the high intensity of autocratic legalism in Indonesia's legislative process. At the same time, legislative products that represent the aspirations of many people remain unfinished, such as the Bill on Indigenous Peoples, the Bill on Asset Forfeiture (related to corruption proceeds), and the Bill on the Protection of Domestic Workers. The problems to be answered in this research consist of two main issues: (1) What is the impact of autocratic legalism on the institutionalization of democracy in Indonesia?, and (2) How does autocratic legalism influence the weakening of civil society consolidation in Indonesia? This research aims to analyze two things, First, why is the institutionalization of democracy difficult to achieve in a situation where autocratic legalism is strengthening, and civil society consolidation is weakening? Second, the impact of autocratic legalism on the weakening of civil society consolidation in Indonesia. This research employs a doctrinal legal method, a conceptual approach, and qualitative analysis. The research findings show that the practice of autocratic legalism, which exploits legal procedures to legitimize power, has made the institutionalization of democracy difficult to function, due to the unsystematic pattern of relations between the executive and legislative branches in law-making, and executive dominance in this practice has reduced the essence of democracy and weakened human rights guarantees through the blurring of checks and balances functions, the strengthening of power coalitions, as well as the criminalization of criticism and restrictions on media freedom. Therefore, the practice of autocratic legalism must be halted through limiting presidential authority, strengthening judicial independence, and increasing meaningful public participation in government oversight.